1990
DOI: 10.1007/bf00318265
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection versus alternative causes of sexual dimorphism in teiid lizards

Abstract: The presence and extent of sexual dimorphisms in body form (size and shape) of adult macroteiid lizards were investigated. Males were significantly larger than females in the temperate species, Cnemidophorus tigris, and in the tropical species, Ameiva ameiva and C. ocellifer. Young adult C. tigris males grew faster than young adult females within and between reproductive seasons. Adult males of all species had larger heads than adult females of the same body size; this difference increased with body size. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
179
1
7

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(197 citation statements)
references
References 64 publications
3
179
1
7
Order By: Relevance
“…The increase of males' head size in sympatry could be explained if interspecific male-male combats take place or if access to females is restrained because of the presence of a closely related species. Although no behavioral studies are available for the populations in question, a bigger head is known to be advantageous in fights between male lizards (Fitch, 1981;Anderson and Vitt, 1990;Mouton and van Wyk, 1993;Perry et al, 2004) and the pattern observed could be the result of the presence of both conspecific and interspecific rivals when both species coexist. The absence of such morphological modifications in females does not contradict such a hypothesis, because there is no evidence for combats between female lizards, at least in these species (Carretero and Kaliontzopoulou, personal observation).…”
Section: Evidence For Sexual and Natural Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of males' head size in sympatry could be explained if interspecific male-male combats take place or if access to females is restrained because of the presence of a closely related species. Although no behavioral studies are available for the populations in question, a bigger head is known to be advantageous in fights between male lizards (Fitch, 1981;Anderson and Vitt, 1990;Mouton and van Wyk, 1993;Perry et al, 2004) and the pattern observed could be the result of the presence of both conspecific and interspecific rivals when both species coexist. The absence of such morphological modifications in females does not contradict such a hypothesis, because there is no evidence for combats between female lizards, at least in these species (Carretero and Kaliontzopoulou, personal observation).…”
Section: Evidence For Sexual and Natural Selectionmentioning
confidence: 99%
“…In many lacertid lizards, as in other lizard families, males present larger body size and head dimensions (Cooper and Vitt, 1989;Anderson and Vitt, 1990;Mouton and van Wyk, 1993;Andersson, 1994;Brañ a, 1996;Herrel et al, 1996Herrel et al, , 1999Herrel et al, , 2001aKratochvil et al, 2003;Molina-Borja, 2003;Uller and Olsson, 2003), while females have a longer trunk (Andersson, 1994;Brañ a, 1996;Butler and Losos, 2002;Olsson et al, 2002;Schwarzkopf, 2005). Moreover, both head dimensions and trunk length have been shown to present a positive allometric relationship with total size in males and females, respectively, offering indirect support of sex-specific selection for these traits (Carothers, 1984;Brañ a, 1996;Hews, 1996;Olsson et al, 2002;Kratochvil et al, 2003).…”
mentioning
confidence: 99%
“…Because males usually arrange their territories to enclose the female's territory and exclude other males from their own territories, females have little opportunity to see more than one male at a time; thus, females tend to be monogamous (Stamps 1983). In non-territorial lizards, however, polygyny often is sequential, with males usually searching for females, and staying with them for various lengths of time after successful mating (Anderson & Vitt 1990, Olsson 1993, Censky 1995, Cooper & Vitt 1997, Olsson & Shine 1998. Because females of these species have the opportunity to mate with several males, the primary mechanism available to males to ensure paternity is to accompany the female and guard her from access by other males (Bull 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of A. ameiva, as in other teiids, the evolution of larger body and head size in males may result from the competitive advantage that larger males gain as access to more females, thereby increasing reproductive success (ANDERSON & VITT 1990). Sexual dimorphism is found in other populations of A. ameiva (ANDERSON & VITT 1990, COLLI 1991, VITT & COLLI 1994, which suggests that this characteristic is conservative along the continuum of habitats of the species range, and is probably an ancestral trait of the Teiidae (ANDERSON & VITT 1990). We conclude that A. ameiva has an extended reproductive period despite the marked seasonality in the restinga habitat at Barra de Maricá.…”
Section: Vitt and Colli 1994)mentioning
confidence: 99%